2004
DOI: 10.1111/j.1572-0241.2004.30368.x
|View full text |Cite
|
Sign up to set email alerts
|

Postpolypectomy Lower Gastrointestinal Bleeding: Potential Role of Aspirin

Abstract: Postpolypectomy bleeding is an uncommon but important complication of endoscopic polypectomy. There was no statistically relevant difference in prior aspirin use before polypectomy in the bleeding group and the matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(102 citation statements)
references
References 24 publications
6
88
0
8
Order By: Relevance
“…According to the guidelines of the American Society for Gastrointestinal Endoscopy (ASGE) (26) as well as other prior studies (12,13), aspirin and other NSAIDs do not increase the risk of significant bleeding after colonoscopic polypectomy; this is in agreement with the univariate analysis result of the present study (12,13). Because more than 90% of our patients stopped medications at least 3 days before polypectomy in this study, we speculate that this interval was adequate to prevent the risk of IPPB.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to the guidelines of the American Society for Gastrointestinal Endoscopy (ASGE) (26) as well as other prior studies (12,13), aspirin and other NSAIDs do not increase the risk of significant bleeding after colonoscopic polypectomy; this is in agreement with the univariate analysis result of the present study (12,13). Because more than 90% of our patients stopped medications at least 3 days before polypectomy in this study, we speculate that this interval was adequate to prevent the risk of IPPB.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have suggested that patient-related factors (e.g., prior aspirin or anticoagulant use) (8)(9)(10), polyp-related characteristics, and procedure-related factors such as the type of electrosurgical current or submucosal injection solution (11) may confer a high risk for PPB (12)(13)(14)(15)(16)(17). Although it has been suggested that patient-related, polyp-related, and procedure-related factors are strongly associated with PPB, few studies have evaluated the potential risk factors for immediate PPB (IPPB) in patients with colorectal polyp, and compared the identified risk factors of patients with and without IPPB, or examined potential risk factors by multivariate analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Studies of aspirin in the context of ESD 29 30 or large (>20 mm) colonic EMRs [31][32][33] have found an increased risk of haemorrhage; EMR in the upper gastrointestinal tract confers a high risk of haemorrhage, but there are no studies on continuous aspirin therapy. The thrombotic risk to the patient should also be considered, particularly in those receiving aspirin for secondary prevention as they are at greater risk from discontinuation of therapy than those taking it for primary prevention.…”
Section: Aspirinmentioning
confidence: 99%